The horror in the museum and other stories - Lovecraft, H. P. (Howard Phillips), 1890-1937.; Elliott, M. J., 1969- (Hertfordshire [England] : Wordsworth Editions, 2011)
With an Introduction by M.J. Elliott. `My eyes, perversely shaken open, gazed for an instant upon a sight which no human creature could even imagine without panic, fear and physical exhaustion...' A wax museum in London boasts a new exhibit, which no man has seen and remained sane... A businessman is trapped in a train carriage with a madman who claims to have created a new and efficient method of capital punishment... A doctor plans a horrible revenge, using as his murder weapon an insect believed capable of consuming the human soul... Within these pages, some of H P Lovecraft's more obscure works of horror and science fiction can be found, including several fantastic tales from his celebrated Cthulhu Mythos. No true Lovecraft aficionado dare be without this volume.
-- The green meadow -- Poetry and the gods -- The crawling chaos -- The horror at Martin's Beach -- Imprisoned with the pharoahs -- Two black bottles -- The thing in the moonlight -- The last test -- The curse of Yig -- The electric executioner -- The mound -- Medusa's coil -- The trap -- The man of stone -- The horror in the museum -- Winged death -- Out of the Aeons -- The horror in the burying ground -- Till A' the seas -- The diary of Alonzo Typer -- Within the walls of Eryx -- The night ocean.
"This collection represents Lovecraft's most significant collaborations, spanning the period from 1918 to 1936. Some of these tales were rewritten by Lovecraft, based upon another author's earlier draft. Others are entirely his work, though credited to someone else"--Introd.
Keywords: Horror tales, American